Pentingnya Kompetensi Kerja Dalam Meningkatkan Kinerja Pegawai Negeri Sipil di Biro Umum dan Keuangan Universitas Sam Ratulangi Manado - Sumendap, Jefri; Mandey, Jantje; Mambo, Rully (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Any public or private organization set up to achieve certain goals, and if achieved then canbe said to be successful. To achieve success, the necessary foundation of competency to be considered,then also increase the performance. Based on strong background in the form of competence. Thus, thecompetence to be very useful to help the organization improve its performance. Competence isindispensable in every process of human resources. The more problems, the study aims to describe theimportance of competence on employee performance.This research uses qualitative research is research that is used to examine the condition of natural objectsin which the researcher is a key instrument. the proper technique to determine the source of the data /informant is "purposive sampling" is penentukan data source based on a specific goal (Sugiono, 2009).Who became an informant or source of the data in this study is the Civil Service Bureau and the PublicFinance Sam Ratulangi University in Manado.The results showed that the competence of work on General Affairs and Finance University of SamRatulangi is still lacking due to the lack of opportunities given to employees to participate in educationand training. Employee performance is still in the category of "moderate" tend to 'low'. It means that theneed for internal policy of the organization to improve employee performance. Job competence of formaleducation aspect, it seems not too important in encouraging the improvement of performance of theapparatus, while aspects danlatihan education and work experience sizeable plays an important role inencouraging the improvement of employee performance and financial General Bureau of Sam RatulangiUniversityKeywords: Competence, Performance Officer